Active learning for the promotion of students' creativity and critical thinking: An experience in structural courses for architecture. (15th July 2019) - Sgambi, Luca; Kubiak, Lylian; Basso, Noemi; Garavaglia, Elsa
Abstract : Purpose: The purpose of this paper is two-fold: first, it highlights the importance of the presence of active teaching experiences in architecture courses. Such experiences can lead to an improvement in the teaching of technical disciplines, such as structural engineering. Second, it purports to demonstrate the relation and interaction between the active teaching strategy here presented and the learning outcomes required by the study programme. Design/methodology/approach: The paper reports an active didactic experience (addressed to students of architecture and performed at Politecnico di Milano, Italy, and Université catholique de Louvain, Belgium), from its conception to its development in the classroom with the students. The experience is reported by discussing the three main steps of which an active didactic experience should be composed: the stimulus, the practice and the discussion. Findings: The experience seeks to find innovative methods to stimulate the study of structural engineering by students of architecture. Through this experience, based on the study of a square silicon pot mat, students are able to learn concepts related to the mechanics of structures. In addition, students find in their experience direct connections with structures of considerable architectural importance, such as the structure of the New National Gallery by Mies van der Rohe. Originality/value: This experience is original in two aspects. First of all, the introduction of an active didactic experience to improve courses that are generally structured in a passive way. Second, in an era where the importance of numerical technology is growing, this experience goes in a different direction by choosing a low-tech but no less interesting approach.